Decision-Making Preferences About Secondary Germline Findings That Arise From Tumor Genomic Profiling Among Patients With Advanced Cancers - Hamilton, Jada G. (JCO Precis Oncol, 2017)
PURPOSE: In patients with advanced cancers, tumor genomic profiling (TGP) can reveal secondary germline findings (SGFs) with regard to inherited disease risks. This study examined the process by which patients with advanced cancers would decide about whether to learn these SGFs and their preferences about specific challenging decision scenarios, including whether patients should be required to receive SGFs and whether SGFs should be returned to the family after a patient’s death. PATIENTS AND METHODS: We conducted qualitative semistructured interviews with 40 patients with advanced breast, bladder, colorectal, or lung cancer who had undergone TGP. Data were collected on participants’ perspectives about the hypothetical decision to learn their SGFs, including their anticipated approach to the decision-making process, and their preferences about challenging decision scenarios. Data were evaluated by thematic content analysis. RESULTS: We identified themes with regard to participants’ preferred degree of decisional autonomy, perceived vital role of doctors, information needs, and anticipated process of deliberation. Although participants reported that this decision was ultimately their own, many wanted input from family and trusted others. Oncologists were expected to provide decision guidance and key clarifying information. Most participants stated that patients should be able to make a choice about receiving actionable SGFs, and a majority stated that SGFs should be available to family after a patient’s death. CONCLUSION: These results provide insight into SGF decision-making processes of patients with advanced cancers, which can allow clinicians to provide patients with optimal decision support in this context. Patients with advanced cancers have specific information needs and decision-making preferences that educational and communication interventions should address to ensure that patients make informed choices about learning SGFs.